2021
DOI: 10.1093/nar/gkaa1269
|View full text |Cite
|
Sign up to set email alerts
|

Non-B DNA: a major contributor to small- and large-scale variation in nucleotide substitution frequencies across the genome

Abstract: Approximately 13% of the human genome can fold into non-canonical (non-B) DNA structures (e.g. G-quadruplexes, Z-DNA, etc.), which have been implicated in vital cellular processes. Non-B DNA also hinders replication, increasing errors and facilitating mutagenesis, yet its contribution to genome-wide variation in mutation rates remains unexplored. Here, we conducted a comprehensive analysis of nucleotide substitution frequencies at non-B DNA loci within noncoding, non-repetitive genome regions, their ±2 kb flan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 150 publications
(155 reference statements)
5
70
1
Order By: Relevance
“…It has been shown that G4 structures are correlated with increased DNA polymerization error rates 49 , and that G4 structures harbor a high incidence of disease-causing point mutations and indels [50][51][52] . Further, studies demonstrate that ATRX mutant tumors carry a high mutation rate either at the single-nucleotide variant level or copy number alterations 25,53 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that G4 structures are correlated with increased DNA polymerization error rates 49 , and that G4 structures harbor a high incidence of disease-causing point mutations and indels [50][51][52] . Further, studies demonstrate that ATRX mutant tumors carry a high mutation rate either at the single-nucleotide variant level or copy number alterations 25,53 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, selective constraints might be more relaxed at G4 versus non-G4 sites in some functional regions, leading to the observed trends. Alternatively, but not exclusively, the increase in polymorphic rate at G4s might be owing to their elevated mutation rate (Guiblet et al 2021).…”
Section: Selection Footprints At G4 Locimentioning
confidence: 99%
“…If stable G4s are functional, then they are expected to be more conserved (i.e., to have lower human-orangutan divergence) than unstable G4s or non-G4 sites. However, elevated mutation rates at G4s, and at stable G4s in particular (Guiblet et al 2021), might also affect divergence. To analyze this effect on divergence, we initially focused on the putatively neutral NCNR, for which selection effects should be minimal.…”
Section: Selection Footprints At G4 Locimentioning
confidence: 99%
See 2 more Smart Citations